Komunikasi Antar Budaya dalam Kerukunan Antar Umat Beragama Islam dan Hindu Desa Suro, Kecamatan Muara Beliti Kabupaten Musi Rawas - Mukhlizar Mukhlizar; Imam Mahdi; Moch Iqbal (Journal on Education, 2024)
This research is motivated by the phenomenon of society in cultural and religious harmony in Dusun 7 Tribina Bali, Suro Village. There are 3 tribes inhabiting the area, namely the Balinese, Javanese, and Suro who are local residents. The problem there has never been research to find out inter-religious harmony in society in cultural and religious harmony. Researchers want to know the analysis of intercultural communication in inter-religious harmony in society using the analysis of George Herbert Mead's theory with the theory of Symbolic Interactionism. The results of the study used the theory of Symbolic Interactionism, namely symbols in achieving inter-religious harmony in the hamlet of 7 Tribina Bali. The rationale for symbolic interactionism: the mind (Mind) of society does not want conflict to occur, so that religious harmony is maintained. Self (Self), namely people who have an attitude of tolerance in the implementation of religious rituals. The community, namely the maintenance of inter-religious harmony in the community, cannot be separated from the support from the Regent government, FKUB, Suro Village government and the wishes of the 7 Tribina Bali hamlet community.